Pengaruh alokasi anggaran sektor pertanian dan industri terhadap PDRB di Kabupaten Kerinci - Aditama, Raches; Ridwansyah, M.; Artis, Dearmi (e-Journal Perdagangan Industri dan Moneter, 2021)
Â  This study aims to analyze the development of the agricultural and industrial sector budgets and analyze the effect of the farming and industrial sector budget allocations on the GRDP in the Kerinci district. The analytical method used is multiple linear regression with Ordinary Least Square (OLS). This study indicates that the development of the industrial sector budget in Kerinci Regency for the 2010 to 2020 period has fluctuated with an average growth of Rp. 36,920,377,491 per year and the average industrial sector budget in Kerinci Regency for the 2010 to 2020 period is Rp. 8,154,752,012 per year. And the results of the analysis of factors that affect GRDP in Kerinci Regency, simultaneously the agricultural and industrial sector budget variables have a significant effect on GRDP, and partially the industrial sector budget has a significant impact. The farm sector budget has no significant effect. Â Keywords: GRDP, Agriculture sector budget, Industry sector budget Â